2010
DOI: 10.1002/adfm.200902336
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quaternary Shape Memory Alloys with Near‐Zero Thermal Hysteresis and Unprecedented Functional Stability

Abstract: Improving the functional stability of shape memory alloys (SMAs), which undergo a reversible martensitic transformation, is critical for their applications and remains a central research theme driving advances in shape memory technology. By using a thin‐film composition‐spread technique and high‐throughput characterization methods, the lattice parameters of quaternary Ti–Ni–Cu–Pd SMAs and the thermal hysteresis are tailored. Novel alloys with near‐zero thermal hysteresis, as predicted by the geometric non‐line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
210
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 336 publications
(217 citation statements)
references
References 31 publications
4
210
2
1
Order By: Relevance
“…In this study, we investigate the composition and thermal process dependent magnetostrictive and microstructural properties of Co 1 − x Fe x alloy thin films, prepared using a co sputtering based composition spread approach 16,[35][36][37] . This technique facilitates syn thesis and screening of large compositional landscapes in indi vidual studies and allows rapid identification of compositions with enhanced physical properties.…”
mentioning
confidence: 99%
“…In this study, we investigate the composition and thermal process dependent magnetostrictive and microstructural properties of Co 1 − x Fe x alloy thin films, prepared using a co sputtering based composition spread approach 16,[35][36][37] . This technique facilitates syn thesis and screening of large compositional landscapes in indi vidual studies and allows rapid identification of compositions with enhanced physical properties.…”
mentioning
confidence: 99%
“…28 It has been reported that the near o1004-oriented single crystal exhibits very large ε SE approaching 10%. 31 If we assume ε SE = 10%, σ Ms = 50 MPa at 4.2 K, temperature-independent σ hys = 20 MPa, and critical slip stress = 500 MPa in the near o1004-oriented single crystal, operations of superelasticity at temperatures up to 366 K and of the EC effect at temperatures as low as T CO = 24 K may be feasible; one specimen can exhibit both superelasticity and the EC effect over a wide temperature window of~340 K. As previously mentioned, the crystallographic compatibility between the parent and martensite phases [10][11][12][13] was considered to be a factor determining the magnitude of the MT temperature hysteresis. Although experimental investigations have not been attempted, this guidance appears to be valid for suppressing σ hys and temperature hysteresis; thus, the existing COP mat metrics ( Figure 5) may be revised for such supercompatible superelastic alloys.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, σ hys in SMAs with large ε SE , for example, in FeNiCoAlTaB, 9 is generally large. Recently, an extremely small temperature hysteresis and thereby excellent fatigue properties were achieved in certain SMAs [10][11][12] because of the very small lattice mismatch between the parent and martensite phases 10,11 or among them and precipitates 12 arising from special relationships intrinsic to their lattice correspondence [10][11][12][13] (termed 'supercompatibility' by James 14 ). Another, more conventional approach involves tailoring the microstructure to reduce intergranular constraints; the fatigue properties of Cu-Al-Mn SMA in the forms of a single crystal, bamboo-like polycrystals, and columnar-oriented polycrystals have been successfully improved while realizing small σ hys and large ε SE .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Furthermore, in addition to a very small hysteresis, SMAs satisfying the compatibility condition have been shown to have very stable functional properties over cycling. 15 So far, most of the SMAs studied that exhibit phase compatibility undergo a cubic to orthorhombic (c-o) martensitic transformation giving rise to 6 variants of martensite described by their respective transformation stretch matrix U i . A matrix U i maps the austenite into one of the martensitic variants and its shape is dictated by the symmetry elements lost by the austenite.…”
Section: Introductionmentioning
confidence: 99%